(untitled) (Mustansiria Dental Journal, 2022)
Aim of the study: The purpose of this research was to see how drying protocols affected the apical sealing of teeth filled with various sealers. Materials and methods: Protaper rotary files were used for root canals instrumentation of ninety teeth with single root canal. According to the drying protocol, the teeth were separated into three groups (n = 30): "GI–paper points"; "GII–ethanol + paper points"; "GIII–EndoVac + paper points". Using a single-cone approach, every group was separated to three subgroups based on the sealer used: BiooRoot sealer, Epoxy resin and zinc oxide eugenol (ZOE), The apical dye penetration in millimeter was examined under a streromicroscope to assess apical seal. The data was submitted to one –way ANOVA and T test. Results: The result showed statistically no significant difference in microleakage between bioRoot and Epoxy resin (p > 0.05) while there was significant differences of microleakage between ZOE and other sealers, and there is no significant difference between drying protocols in canals obturated with each used sealers (BioRoot, Epoxy resin and ZOE). Conclusion: Drying protocols have no effect on the apical seal of the tested sealers.